Estudio bibliográfico de Leucemia felina en gatos del Ecuador - Villarroel Jimenez, Kasandra Analia (2023)
The research was carried out with the objective of bibliographic study of Leukemia in cats in Ecuador. The present research was documentary, applying the inductive-deductive method, where information was collected such as sources of degree works, scientific articles, internet documents, etc. The data results showed that this disease is relatively common in domestic cats as well as stray cats due to lifestyle and exposure from living on the streets. Feline leukemia can have serious consequences for the health of stray cats if preventive measures are not taken. There is currently no cure for leukemia but treatment is available to control symptoms and improve quality of life. Prevention is the best way to avoid disease and can be achieved through vaccination and limiting contact with infected cats. According to the findings, the prevalence in Santo Domingo reached a total of 68.1%, while in the city of Guayaquil it was evident that 71.43% presented symptoms such as gingivitis and 85.71% had reactive lymph nodes, resulting in a positive result. virus, and a study carried out in the city of Quito where 384 blood samples were analyzed for feline leukemia showed 20.3% (78 cats) positive and 79.7% (306 cats) negative. In conclusion, this research provides valuable information about leukemia in cats in Ecuador; the results highlight the importance of vaccination with a health plan and prevention to reduce this disease in the feline population.